﻿Beyond the species name: an analysis of publication trends and biases in taxonomic descriptions of rainfrogs (Amphibia, Strabomantidae, Pristimantis) - Carolina Reyes-Puig; Emilio Mancero (ZooKeys, 2022)
The rainfrogs of the genus Pristimantis are one of the most diverse groups of vertebrates, with outstanding reproductive modes and strategies driving their success in colonizing new habitats. The rate of Pristimantis species discovered annually has increased continuously during the last 50 years, establishing the remarkable diversity found in this genus. In this paper the specifics of publications describing new species in the group are examined, including authorship, author gender, year, language, journal, scientific collections, and other details. Detailed information on the descriptions of 591 species of Pristimantis published to date (June 2022) were analyzed and extracted. John D. Lynch and William E. Duellman are the most prolific authors, yet Latin American researchers have scaled up and continued the description processes since the 1990s. The most common language used for descriptions is English, followed by Spanish. The great majority of authors have described only one species. The largest proportion of authors who have participated in the descriptions is of Ecuadorian nationality. Ecuador is the country with the highest description rate per year (3.9% growth rate). Only 20% of the contributions have included women and only 2% have featured women as principal authors. 36.8% of the species described are in the Not Evaluated or Data Deficient categories under the IUCN global red list. The importance of enhancing the descriptions in Spanish is emphasized and the inclusion based on equal access to opportunities for female researchers in Pristimantis taxonomy is encouraged. In general, if the current trends in Pristimantis descriptions continue, in ten years, a total of 770 or more species described could be expected.